2019
DOI: 10.1002/tcr.201900046
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in the Field of Adsorption and Catalytic Degradation of Sewage by Hydrotalcite‐Derived Materials

Abstract: With the rapid development of industry and agriculture and the greatly improved living conditions, the resultant gradually deteriorated environments threaten the human beings. Refractory or even toxic pollutants, which are from different industries such as printing and dyeing, pesticides, chemicals, petrochemicals, plastics and rubber, seriously threat the ecosystems and human health. Having the advantages of flexible composition, unique structure, high stability, memory effect, easy preparation and low cost, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 158 publications
0
13
0
Order By: Relevance
“…The superior physicochemical properties of molecular sieve catalysts not only make them commonly used in waste plastic catalytic pyrolysis, but also in petroleum sludge catalytic pyrolysis. [76] Silva et al [77] studied the thermal decomposition products of petroleum sludge in the presence or absence of Y zeolite catalyst. It was found that Y zeolite catalyst can better distribute Liquid Petroleum Gas (LPG) products-gasoline and diesel at different temperatures (Fig.…”
Section: Mesoporous Molecular Sieve Catalystsmentioning
confidence: 99%
“…The superior physicochemical properties of molecular sieve catalysts not only make them commonly used in waste plastic catalytic pyrolysis, but also in petroleum sludge catalytic pyrolysis. [76] Silva et al [77] studied the thermal decomposition products of petroleum sludge in the presence or absence of Y zeolite catalyst. It was found that Y zeolite catalyst can better distribute Liquid Petroleum Gas (LPG) products-gasoline and diesel at different temperatures (Fig.…”
Section: Mesoporous Molecular Sieve Catalystsmentioning
confidence: 99%
“…[221] Various methods have been attempted to improve the corrosion resistance of organic coatings, among which the introduction of nano-fillers into organic coatings is determined to be an effective method to improve the anticorrosive performance. [222][223][224] Since BN has hydrophobicity, inertness and dielectric properties, [225] especially high electronegativity of nitrogen atoms, [25,226] galvanic corrosion is less likely to occur between BN and the underlying metal matrix. [227] Cui et al [228] achieved a stable dispersion of h-BN nanosheets in organic coatings by using carboxylated aniline trimer (CAT) as a non-covalent dispersant.…”
Section: Anticorrosive Materialsmentioning
confidence: 99%
“…However, the evaporation of solvent during the film formation or prolonged exposure to air after coating may result in the formation of micropores within the organic coating, which results in coating damage and metal corrosion [221] . Various methods have been attempted to improve the corrosion resistance of organic coatings, among which the introduction of nano‐fillers into organic coatings is determined to be an effective method to improve the anticorrosive performance [222–224] . Since BN has hydrophobicity, inertness and dielectric properties, [225] especially high electronegativity of nitrogen atoms, [25,226] galvanic corrosion is less likely to occur between BN and the underlying metal matrix [227] …”
Section: The Applications Of Boron Nitride and Its Derived Nanomaterialsmentioning
confidence: 99%
“…Low-dimensional nanomaterials have attracted widespread attention due to their excellent electrical, thermal, and mechanical properties. Carbon nanotubes, graphene, and their derivatives with a strong and single-atom-thick crystal of bonded carbon can be directly grown on selected metals or transferred to arbitrary substrates and are nonreactive with most chemicals; thus, they have been used as surface coating fillers on metals to prevent oxidation and corrosion. , However, the long-term immersion of these carbon materials in corrosive media may cause galvanic corrosion of metal substrates, thereby accelerating metal corrosion . Two-dimensional nanomaterial boron nitride nanosheets (BNNSs) are layered structure materials composed of B atoms and N atoms stacked by covalent bonds. Especially, both excellent chemical stability and high insulation make them have potential anticorrosion applications. There are two main methods for preparing BNNSs.…”
Section: Introductionmentioning
confidence: 99%